Pelatihan Pencatatan Barang dan Keuangan Menggunakan Microsoft Excel Serta Penginputan Harga Barang ke Website bagi Pegawai Fitry Bakery & Cake - Syamsuddin Mas'ud; Andika Saputra (Jurusan Matematika FMIPA UNM, 2024)
The community service activity conducted involved training in inventory recording, financial recording, and inputting product prices for the employees of Fitry Bakery & Cake, a business unit located in Gowa. The aim of this training was to improve efficiency and accuracy in inventory and financial management using Microsoft Excel, as well as updating product prices on their website aplikasi. The training was conducted online via Google Meet on December 30, 2023, and lasted for one day. After participating in the training, all participants demonstrated a good understanding of the material presented. In the introduction to Microsoft Excel, participants were able to understand and use the Excel interface and basic functions such as SUM, AVERAGE, and IF. For inventory recording, participants successfully managed inventory tables using filter and sort features and recorded product details accurately. In financial recording, participants were able to create and perform financial recapitulation. As for inputting product prices on the website aplikasi, participants successfully simulated inputting product prices on the website aplikasi effectively.